Valorization of wild species Cardaria draba (L.) Desv.: primary metabolites, mineral content, and fatty acid profile - Wissal SAADELLAOUI; Yassine MRABET; Mohamed Ali BENABDERRAHIM; Abir HADDADA; Nourhen HAMMAMI; Khaled NASRI; Abdelaziz SEBEI; Fethia HARZALLAH-SKHIRI; Karim HOSNI; Sondes STAMBOULI-ESSASSI (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
The aim of this research was to assess the proximate (ash, organic matter, fiber, protein, sugars, starch, and carbohydrates) and minerals (K, Ca, Mg, P, Na, S, Fe, Zn, Cu, Mn, Cd, Co, Cr, Pb, and Ni) compositions of Tunisian wild Cardaria draba (L.) Desv. organs (roots, stems, leaves, flowers, and fruits) using standard methods. The profile of fatty acids was assessed through gas chromatography with flame ionization detection (GC-FID) with lipid quality evaluation. Results show that leaves have the highest ash (19.20 g/100 g dw) and protein (38.90 g/100 g dw) contents, while roots are richest in fiber (32.80 g/100 g dw) and soluble sugars (9.68 g/100 g dw). Flowers and fruits contain the most starch contents (56.96 and 51.22 g/100 g dw, respectively). Leaves also have the highest concentrations of K, Ca, Mg, Na, and P, while fruits and flowers have the highest sulfur content (478.98 and 432.50 mg/100 g dw, respectively). Fe is primarily found in leaves and stems (37.50 and 36.98 mg/100 g dw), Mn in stems (5.35 mg/100 g dw), and Zn in leaves (4.21 mg/100 g dw). Roots accumulate the most trace elements, remaining below toxicity limits. Fruits have the highest oil content (12.50%). Unsaturated fatty acids (UFA) dominate, with oleic acid (29.38%) as the main in roots, α-linolenic acid (12.98%) in aerial parts, and linoleic acid (7.94%) in fruits oils. Erucic acid is highest in fruits (7.70%) but undetectable in aerial parts. Palmitic and stearic acids, are highest in roots (22.05% and 23.18%, respectively). The oils demonstrate high nutritional quality, with favorable hypocholesterolemic properties (h/H ratio of 1.67 to 2.30) and low atherogenic (0.50-0.62) and thrombogenic (0.22-1.00) indices. These results indicate that C. draba organs are a valuable source of essential nutrients and fats, with potential applications in diet, health, cosmetics, and biodiesel.